2021
DOI: 10.1016/j.cmet.2021.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Host-microbial interactions in the metabolism of different dietary fats

Abstract: Although generally presumed to be isocaloric, dietary fats can differ in their energetic contributions and metabolic effects. Here, we show how an explicit consideration of the gut microbiome and its interactions with human physiology can enrich our understanding of dietary fat metabolism. We outline how variable human metabolic responses to different dietary fats, such as altered ileal digestibility or bile acid production, have downstream effects on the gut microbiome that differentially promote energy gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 204 publications
(258 reference statements)
1
39
0
Order By: Relevance
“…In this sense, our results on miRNAs could reflect the gut microbiota shifts in response to dietary fat recently reviewed by Chadaideh and Carmody. 76 In the present study, among the three investigated groups, the analysis of the dietary information recorded in the EPIC questionnaires confirmed the expected differences in weekly food consumption and estimated daily nutrient intake. Nutrients and specific diet components have been implicated in the modulation of miRNA expression in in vitro/in vivo models and, as a consequence, in all miRNA-mediated molecular mechanisms.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this sense, our results on miRNAs could reflect the gut microbiota shifts in response to dietary fat recently reviewed by Chadaideh and Carmody. 76 In the present study, among the three investigated groups, the analysis of the dietary information recorded in the EPIC questionnaires confirmed the expected differences in weekly food consumption and estimated daily nutrient intake. Nutrients and specific diet components have been implicated in the modulation of miRNA expression in in vitro/in vivo models and, as a consequence, in all miRNA-mediated molecular mechanisms.…”
Section: Discussionsupporting
confidence: 84%
“…In this sense, our results on miRNAs could reflect the gut microbiota shifts in response to dietary fat recently reviewed by Chadaideh and Carmody. 76 …”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota participates in host metabolism by interacting with host signaling pathways ( 16 ). Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of changed microbiota genes indicated that eight major signaling pathways were upset by HFD and recovered by A10-FMT and/or Con-FMT in the colon, cecum, and/or small intestine ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2J ). It is known that HFD upsets lipid metabolism because the host and gut microbiota interact together to support this process ( 16 ). Furthermore, it has been reported that the gut microbiota Mucispirillum is involved in lipid metabolism ( 2 , 12 ), and it was increased by HFD while decreased by A10-FMT.…”
Section: Resultsmentioning
confidence: 99%
“…In animal models, changes to the gut microbiome can substantially alter weight gain and obesity, without changes in total energy intake or physical activity ( 16 , 17 ); and changes in both absolute and relative microbiome energy use influence host weight gain ( 10 , 11 ). Such complexity also extends to different dietary fats, whose effective caloric value, for the host, may vary depending on the type of food consumed and host–microbial interactions ( 18 ). In sum, a differential partitioning of consumed energy, due to population changes in foods consumed and microbial characteristics, could be a contributor to the obesity epidemic.…”
Section: The Obesity Epidemic: Changing Biology?mentioning
confidence: 99%